Local Government Responses to HIV and AIDS in the Border Areas: A Case Study of Batam - Augustina Situmorang; Sri Sunarti Purwaningsih (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2010)
-